THE INFLUENCE OF OWNERSHIP STRUCTURE, FIRM SIZE, AND CAPITAL STRUCTURE ON CSR DISCLOSURE - Gilang, Sabrang Gilang Gemilang; Dewi, Resti Kartika; Reza, Muhammad Helmy (UIR Press, 2025)
This research examines the influence of share ownership structure, company size and capital structure on corporate social responsibility (CSR) disclosure. The research method used is a quantitative method. The population used in this research were 45 companies listed on the LQ-45 Index of the Indonesian Stock Exchange. The analytical method used in this research is multiple linear regression. The results of this research show that share ownership structure, company size and capital structure have no effect on corporate social responsibility (CSR) disclosure. This shows that CSR disclosure has become an important requirement for all companies listed on the LQ-45 index to be carried out without being influenced by the factors above.